Sectoral Output Responses to Trade Openness, Oil Price and Policy Shocks in Nigeria: A CVAR Approach - O., Saibu M. (Journal of Social and Development Sciences, 2011)
This study investigated the relative effectiveness of trade and policy shocks on sectoral output growth in a small open Nigerian economy. It is a country-specific, time series study verifies whether there is difference in the effect of sectoral output response to policy shocks in Nigeria. A CVAR model was specified to assess the effects of policy shocks on real aggregate and sectoral output measures. The model included oil price shock and an interactive term of trade openness as measures of supply and external shocks to the economy. The empirical results showed that there was remarkably difference in sectoral output responses to policy distortion. The effects of monetary policy shocks were positive and significant on manufacturing, service and industrial sector while fiscal policy shock was only significant and positive on agricultural output growth. The result further showed that international oil price shock and trade openness had pronounced negative effects on both sectoral and aggregate outputs. In addition, oil and trade openness’ negative effects overwhelmed the positive effects of fiscal and monetary policy shocks. The policy implication of the finding is that the effectiveness of domestic macroeconomic policy is constrained by the external shocks from both oil price and trade openness. Thus, confirming the open economic version of policy ineffectiveness proposition of the New classical macroeconomic in Nigeria